A Short Appendix to Richard Lavenham’s Tractatus terminorum naturalium - Hanke, Miroslav (Vivarium, 2024)
Continuing the tradition of Oxford Calculatorial physics, the late fourteenth-century British Carmelite Richard Lavenham authored an amplification of the popular short textbook commonly referred to as Termini naturales. A copy of this amplification, preserved in a late fourteenth-century manuscript (Venezia, Biblioteca Nazionale Marciana, ms Lat. Z. 300 [= 1872]), is followed by a short series of notes and comments on some of the principles introduced in Lavenham’s treatise (drawn from the first four books of Aristotle’s Physics). The present article offers an edition of the text, and analyses its content and relationship with fourteenth-century physics, especially with the physical doctrines of Richard Lavenham.